PENGARUH TEKANAN ANGGARAN WAKTU PADA STRESS KERJA DAN DAMPAKNYA TERHADAP PERILAKU REDUKSI KUALITAS AUDIT - I Gusti Ayu Ratih Permata Dewi; L.G.P. Sri Eka Jayanti (Faculty of Economics and Business, Universitas Warmadewa, 2021)
This study aims to analyze Time Budget Pressure on Work Stress and its Implications for Audit Quality Reduction Behavior. This research was conducted at a registered public accounting firm in Bali using a questionnaire distributed to auditors who are at least the team leader in audit assignments. The data analysis technique used is the Partial Least Square (PLS) approach. The results showed that audit time budget pressure has a positive effect on job stress.Furthermore, job stress and audit time budget pressure have a positive effect on audit quality reduction behavior. The results also show that job stress is able to mediate the effect of audit time budget pressure on audit quality reduction behavior.